Physiological and yield responses of mung bean (vigna radiata (l.) Wilczek) genotypes under irrigated and rainfed water regimes during the minor rainy season (yala) in the low country dry zone of Sri Lanka - Eeswaran, R.; Weerakoon, W.M.W.; Sangakkara, U.R. (University of Peradeniya, 2012)
Mung bean (Vigna radiata) is a popular food legume and commonly grown as a rainfed crop or with supplementary irrigation in the minor rainy season (Yala) of the dry zone, where unexpected terminal droughts are becoming prominent due to climate change. Therefore, this field study evaluated the physiology and yield related performances of some mung bean genotypes under two water regimes during the Yala season in the dry zone as a part of selecting stress tolerant crop genotypes to sustain yields.